Elucidation of short linear motif-based interactions of the MIT and rhodanese domains of the ubiquitin-specific protease 8 - Aimiliani Konstantinou; Julia K. Varga; Alicia Córdova-Pérez; Leandro Simonetti; Lidia Gomez-Lucas; Ora Schueler-Furman; Norman E. Davey; Yogesh Kulathu; Ylva Ivarsson (Biology Direct)
Abstract Ubiquitin-specific protease 8 (USP8) is a deubiquitinating enzyme with essential functions in protein trafficking and stability. It is a multidomain protein, with an N-terminal MIT (microtubule interacting and trafficking) domain, followed by a non-catalytic rhodanese (Rhod) domain, a long intrinsically disordered region, and a C-terminal catalytic domain. The N-terminal MIT domain of USP8 is known to mediate protein-protein interactions through binding to short linear motifs. The non-catalytic Rhod domain is also involved in protein-protein interactions, however detailed insights into these interactions remain limited. In this study we explore the short linear motif-based interactions of the MIT and Rhod domains of USP8 using a combination of proteomic peptide-phage display, peptide arrays and deep mutational scanning. We show that the MIT domain can bind ligands with a general [DE][LIF]x{2,3}R[FYIL]xxL[LV] consensus motif. We uncover that the rhodanese domain of USP8 is a peptide-binding domain, and define two distinct binding motifs (Rx[LI]xGxxxPxxL and G[LV][DE][IM]WExKxxxLxE) for this domain by deep mutational scanning of two different peptide ligands. Using the motif information, we predict binding sites within known USP8 interactors and substrates and validate interactions through peptide array analysis. Our findings demonstrate that both the USP8 MIT and rhodanese domains are peptide-binding domains that can be bound by degenerate and distinct binding motifs. The detailed information on the peptide binding preference of the two N-terminal domains of USP8 provide novel insights into the molecular recognition events that underlie the function of this essential deubiquitinating enzyme.